IMPACT OF HEDONIC LIFESTYLE THROUGH BRAND IMAGE ON INTEREST OF GOPAY USERS IN GENERATION Z IN BEKASI CITY - Meistoh, Siti; Hadita, Hadita (Dinasti Publisher, 2022)
The purpose of this study was to determine the impact of the hedonic lifestyle through brand image on the interest of Gopay users in Generation Z. The method used in this study was the quantitative method, which in this study used the Accidental Sampling technique in determining the sampling method. The basis of the study used 150 respondents to be used as samples in the study, where in this study used primary data obtained by distributing questionnaires to Gopay User Interests in Generation Z. The results of this study indicate that 1). Hedonic Lifestyle has no significant effect on User Interests, 2). Hedonic Lifestyle has a significant effect on the intervening variable Brand Image, 3). Brand Image has a significant effect on the User Interest variable 4). Hedonic Lifestyle significantly succeeded in mediating Brand Image on User Interest.